2015
DOI: 10.1128/jb.02346-14
|View full text |Cite
|
Sign up to set email alerts
|

Cj1386, an Atypical Hemin-Binding Protein, Mediates Hemin Trafficking to KatA in Campylobacter jejuni

Abstract: . While the structure and biochemical properties of catalase enzymes have been well characterized over many decades of research, it remained unclear how catalases acquire hemin. We have previously reported that Cj1386 is essential for ensuring proper hemin content in Campylobacter jejuni catalase (KatA) (A. Flint, Y. Q. Sun, and A. Stintzi, J Bacteriol 194:334 -345, 2012). In this report, an in-depth molecular characterization of Cj1386 was performed to elucidate the mechanistic details of this association. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…The immediate upstream ORF (LIMLP_10150), encoding an ankyrin repeat-containing protein, was also up-regulated with a comparable fold. In bacteria such as Pseudomonas aeruginosa and Campylobacter jejuni, protein with ankyrin repeats were found to be required for the catalase activity, probably by allowing heme binding (19,20). In L. interrogans, katE and ank were organized as an operon (S1 Fig) and significant up-regulation of the ank-katE operon upon exposure to sublethal dose of H 2 O 2 was confirmed by RT-qPCR (Table 1 and S1 Fig).…”
Section: Resultsmentioning
confidence: 85%
“…The immediate upstream ORF (LIMLP_10150), encoding an ankyrin repeat-containing protein, was also up-regulated with a comparable fold. In bacteria such as Pseudomonas aeruginosa and Campylobacter jejuni, protein with ankyrin repeats were found to be required for the catalase activity, probably by allowing heme binding (19,20). In L. interrogans, katE and ank were organized as an operon (S1 Fig) and significant up-regulation of the ank-katE operon upon exposure to sublethal dose of H 2 O 2 was confirmed by RT-qPCR (Table 1 and S1 Fig).…”
Section: Resultsmentioning
confidence: 85%
“…Exposure of C. jejuni perR mutants to hydrogen peroxide on discs revealed that the level of peroxide resistance was considerably higher than previously reported, where 3 % hydrogen peroxide was used (Baillon et al, 1999;Flint & Stintzi, 2015;Palyada et al, 2009;van Vliet et al, 1999). Wild-type C. jejuni were sensitive to 5 % H 2 O 2 (Fig.…”
mentioning
confidence: 50%
“…More importantly, the high levels of, especially, catalase resulted in a significant increase in resistance against hydrogen peroxide, with the perR mutant able to grow close to discs infused with 30 % (8.8 M) hydrogen peroxide, which is the highest commercially available concentration of hydrogen peroxide. This concentration is much higher than previously tested, where either 3 % hydrogen peroxide was used (Baillon et al, 1999;Flint & Stintzi, 2015;Palyada et al, 2009;van Vliet et al, 1999), or concentrations ranging from 1-5 mM (Huergo et al, 2013;Hwang et al, 2011a, b), and highlights the very high levels of catalase expression in the perR mutant. A similar phenotype (albeit not as striking) was observed (Chaudhuri et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Characterisation of the Cj1386 protein revealed that it binds haem b at a 1:1 ratio and that it interacts with KatA (Flint and Stintzi 2015). Similarly to H. pylori KapA, Cj1386 did not show catalase activity, but was found to indirectly contribute towards optimal catalase activity within cells (Flint, Sun and Stintzi 2012).…”
Section: Catalase (Kata) and Catalase Accessory And Biogenesis Proteimentioning
confidence: 97%
“…Furthermore, these catalase-negative strains lack homologues of the haem-trafficking protein, cj1386 (Flint and Stintzi 2015). Recently, Koolman et al have investigated the presence of sodB and katA by PCR in 24 Campylobacter isolates obtained from poultry or human origin belonging to the C. jejuni, C. coli and C. lari species.…”
Section: Stress Defences Of Other Helicobacter and Campylobacter Sppmentioning
confidence: 99%